COMMUNICATIVE FUNCTIONS USED IN POPE’S 2021 SPEECH IN IRAQ: A CRITICAL DISCOURSE ANALYSIS OF RELIGIOUS PLURALISM - Hussein, Abber Khalaf; Hazem, Ali Hussein; Kamil, Dina Fahmi (Islam Futura, 2025)
The ongoing state of religious diversity leads to the need of adhering interfaith dialogue as a means for achieving religious pluralism that encourages and promotes respect and acceptance of freedom of religion. Pope Francis’s (2021) speech delivered in the historical City of Ur, Iraq is a call for such pluralism. In this study, it is hypothesised that Pope has focused on the communicative functions that enhance religious diversity acceptance. The study aims at finding out the communicative functions employed in Pope’s speech. In order to achieve this aim, Gerard Genette’s theory of narratology (1980) is adopted. Based on the findings of the analysis, it is concluded that various communicative functions are utilized: narrative, directing, communication, and ideological. Mostly used one is the communication function which is critical in transmitting the fundamental message of unity, peace, and brotherhood. This function is critical for engaging the audience and instilling a sense of shared responsibility for promoting tolerance and peace among religious communities. Consequently, the conclusions arrived at affirm the put hypotheses.